Pelaksanaan Quiz Beserta Umpan Balik Menggunakan Aplikasi Kahoot dalam Pembelajaran Seni Tari di SMA Negeri 4 Kerinci - Shocia Septipa; Marzam Marzam (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This study aims to determine the implementation of Dance Arts learning activities as well as supporting and inhibiting factors in the implementation of Dance Arts learning activities by using the Kahoot Application to increase the learning motivation of Class XI MIPA students at SMA Negeri 4 Kerinci. This type of research is qualitative research with a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps to analyze data are data collection, data reduction, data display and data inference. The results of the study show that the use of Kahoot application media in Dance Arts learning is aimed at increasing students' learning motivation. There is an additional value so that this motivates students to learn so that they can play the Kahoot application well. In addition, this game can also help students to strengthen their memory of the material that has been delivered by the teacher. By using the Kahoot App, students can actively participate in answering questions. The Kahoot app motivates and activates student learning as it can test their knowledge, repeat important concepts, create class discussions and student-to-student interactions. The supporting factor for the use of Kahoot application media in learning Dance Arts is the availability of adequate facilities and infrastructure such as Wi-Fi, lcd projectors, and so on. Then there is also the enthusiasm of students when playing games on the Kahoot application so that it gives a positive response and can facilitate the learning process. Meanwhile, the inhibiting factor for the use of Kahoot application media in Dance Arts learning is a poor signal connection that causes learning to be hampered.